2020
DOI: 10.3389/fchem.2019.00887
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Core-Branch α-Fe2O3@NiO/Carbon Cloth Heterostructured Electrodes for Flexible Supercapacitors

Abstract: A convenient and scalable hydrothermal method was developed for the fabrication of the core-branch Fe 2 O 3 @NiO nanorods arrays directly grown on flexible carbon cloth (denoted as Fe 2 O 3 @NiO/CC). Such a unique architecture was applied as an electrode of the supercapacitors. As a result, the Fe 2 O 3 @NiO/CC exhibited a high areal capacitance ∼800 mF cm −2 at 10 mA cm −2 , which was about 10 times increase with respect to Fe 2 O 3 nanorods array grown on carbon cloth (Fe 2 O 3 /CC). The Fe 2 O 3 @NiO/CC als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…26, Copyright 2018 Wiley, C, TEM images showing the comparison of raw red mud in the raw, unprocessed state (a‐b) and (c‐d) after 10‐hour ball milling, spherical NPs have been obtained, image adapted with permission from Ref. 29, Copyright 2019 Wiley [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Sources Processing and Applications Of Inorganic Wastementioning
confidence: 99%
See 2 more Smart Citations
“…26, Copyright 2018 Wiley, C, TEM images showing the comparison of raw red mud in the raw, unprocessed state (a‐b) and (c‐d) after 10‐hour ball milling, spherical NPs have been obtained, image adapted with permission from Ref. 29, Copyright 2019 Wiley [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Sources Processing and Applications Of Inorganic Wastementioning
confidence: 99%
“…The waste‐derived porous activated material, therefore, can be used as an effective negative electrode for flexible energy storage applications. But, it is to be noted that a similar material (the core‐branch Fe 2 O 3 @NiO nanorods arrays directly grown on flexible carbon cloth) synthesized using hydrothermal route exhibited better performance with an exceptional cycling performance of 96.8% initial capacitance retention at a current density of 20 mA cm −2 even after 16 000 cycles 29 …”
Section: Sources Processing and Applications Of Inorganic Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Carbon materials play a role as negative electrodes, using the electrical double layer to accumulate energy, while the specific capacitance is trapped at an intermediate level of 100-200 F g −1 (Zhu et al, 2011;Sahu et al, 2017;Wang et al, 2019). Recent studies have reported that pseudocapacitive anodes can deliver higher charge storage capacities than carbon materials, such as MoO 3 (Zhang et al, 2019), V 2 O 5 (Guo et al, 2015), WO 3 (Yun T. G. et al, 2019), TiN Sun et al, 2020, Fe 3 (Arun et al, 2019), FeOOH (Chen et al, 2016), and Fe 2 O 3 (Yun X. et al, 2019;Le et al, 2020;Zhang et al, 2020). Among them, α-Fe 2 O 3 is chosen as a potential candidate for ASCs because of its natural abundance, eco-friendly nature, excellent physicochemical stability, large theoretical capacitance (∼3,625 F g −1 ), and high hydrogen evolution potential in aqueous solution (Han et al, 2014;Nithya and Arul, 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…3c, we have observed that CFV x displays improved area specific capacitance and rate property compared to previously estimated vanadium-based, iron-based electrode materials. 20–24 The CFV x electrode also displays an outstanding cycling property with a capacitance retention of 97.14% over 12 000 cycles (Fig. 3e).…”
mentioning
confidence: 97%